Saturation and self‐absorption effects in the angle‐dependent 2p3d resonant inelastic X‐ray scattering spectra of Co3+. (9th June 2020) - Wang, Ru-Pan; Elnaggar, Hebatalla; Titus, Charles J.; Tomiyasu, Keisuke; Geessinck, Jaap; Koster, Gertjan; Frati, Federica; Okamoto, Jun; Huang, Di-Jing; de Groot, Frank M. F.
Abstract : It is shown that the 2 p 3 d resonant inelastic X‐ray scattering intensity is distorted by saturation and self‐absorption effects, i.e. by incident‐energy‐dependent saturation and by emission‐energy‐dependent self‐absorption. Abstract : Angle‐dependent 2 p 3 d resonant inelastic X‐ray scattering spectra of a LaCoO3 single crystal and a 55 nm LaCoO3 film on a SrTiO3 substrate are presented. Theoretical calculation shows that, with ∼20 meV resolved Co 2 p 3 d resonant inelastic X‐ray scattering (RIXS), the excited states of the isotropic 1 A1 g (O h ) ground state are split by 3 d spin–orbit coupling, which can be distinguished via their angular dependence. However, strong self‐absorption and saturation effects distort the spectra of the LaCoO3 single crystal and limit the observation of small angular dependence. In contrast, the RIXS on 55 nm LaCoO3 shows less self‐absorption effects and preserves the angular dependence of the excited states.